2021
DOI: 10.33245/2310-4902-2021-165-1-79-91
|View full text |Cite
|
Sign up to set email alerts
|

Features of clinical and pathomorphological picture in spontaneous infection of a domestic cat (lat. Félis cátus) with SARS-CoV-2 coronavirus

Abstract: Today, cases of infection of various animal species with the new SARS-CoV-2 coronavirus have become increasingly common. This virus has been isolated from numerous representatives of the feline family, European mink, ferret, raccoon dog, domestic dog, a number of primates and a number of other animals. In most susceptible animals, infection with this virus is manifested by certain clinical symptoms, the intensity of which depends on the type and age of the animals, on the presence of concomitant diseases. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The duration of clinical symptoms reported in the different studies varied greatly from a few days to a few weeks. The longest duration of symptoms was recorded by Natale et al [ 32 ], who reported 2 weeks of symptoms in one case and Subotsina et al Subotsina, Gromov and Kupryianav [ 38 ], who found an average symptom duration of 2–3 weeks in 15 examined cases.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The duration of clinical symptoms reported in the different studies varied greatly from a few days to a few weeks. The longest duration of symptoms was recorded by Natale et al [ 32 ], who reported 2 weeks of symptoms in one case and Subotsina et al Subotsina, Gromov and Kupryianav [ 38 ], who found an average symptom duration of 2–3 weeks in 15 examined cases.…”
Section: Resultsmentioning
confidence: 98%
“…Brandão et al [ 19 ], Fritz et al [ 50 ], and Gargliany et al [ 47 ] generically reported respiratory symptoms, while Neira et al [ 33 ], Pagani et al [ 34 ], and Zoccola et al [ 42 ] reported mild respiratory symptoms. Other studies more specifically described sneezing, coughing, and/or shortness of breath [ 27 , 28 , 38 , 44 ]. Some cats developed symptoms of pneumonia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations